Proceso atención de enfermería en paciente pediátrico con linfadenitis aguda. - Rea Zapata, Gissela Johanna (2023)
The present clinical case is focused on a 5-year-old male patient who presented a clinical picture ± 3 days of evolution characterized by hyperthermia of 40ºC, diaphoresis, joint pain, odynophagia, erythema, purulent discharge, tenderness and heat in a localized palpable mass. on the left side of the infrahyoid region of the neck. Taking vital signs showed blood pressure 92/60mm Hg, heart rate 95rxm, respiratory rate 25rxm, oxygen saturation 98%, body temperature 40ºC with a weight of 22kg and a height of 110cm. A peripheral line is placed and IV paracetamol is administered to lower body temperature and treatment with broad-spectrum antibiotics. Physical assessment is performed using Marjorie Gordon's functional patterns in order to identify dysfunctional patterns that are compromising the patient's state of health. For this reason, the Nursing Care Process was elaborated in order to provide the adequate care required by the patient during their hospitalization, and thus meet the objectives proposed in this case study.